The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/bcp.15485
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive pharmacogenomic study indicates roles for SLCO1B1, ABCG2 and SLCO2B1 in rosuvastatin pharmacokinetics

Abstract: Aims The aim was to comprehensively investigate the effects of genetic variability on the pharmacokinetics of rosuvastatin. Methods We conducted a genome‐wide association study and candidate gene analyses of single dose rosuvastatin pharmacokinetics in a prospective study (n = 159) and a cohort of previously published studies (n = 88). Results In a genome‐wide association meta‐analysis of the prospective study and the cohort of previously published studies, the SLCO1B1 c.521 T > C (rs4149056) single nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 65 publications
7
23
0
Order By: Relevance
“…In a previous clinical study, the BCRP‐inhibiting drug febuxostat increased the C max and AUC of rosuvastatin 2.1‐fold and 1.9‐fold 17 . Similarly, the ABCG2 c.421A/A genotype that predicts poor BCRP function has been associated with a 2.0–2.2‐increased AUC of rosuvastatin 22,37 . The effect size of ticagrelor on rosuvastatin pharmacokinetics in this study was in the vicinity of these previous findings.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In a previous clinical study, the BCRP‐inhibiting drug febuxostat increased the C max and AUC of rosuvastatin 2.1‐fold and 1.9‐fold 17 . Similarly, the ABCG2 c.421A/A genotype that predicts poor BCRP function has been associated with a 2.0–2.2‐increased AUC of rosuvastatin 22,37 . The effect size of ticagrelor on rosuvastatin pharmacokinetics in this study was in the vicinity of these previous findings.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, a single oral dose of the OATP‐ and BCRP‐inhibitor rifampicin has increased rosuvastatin concentrations more than fourfold 19 . Similarly, genetically poor BCRP or OATP1B1 function associate with markedly increased rosuvastatin concentrations 20–23 …”
mentioning
confidence: 99%
“…Impaired OATP1B1 function should theoretically reduce the clearance and increase the plasma exposure (AUC 0–∞ ) of rosuvastatin because it decreases its entry into the liver, its main site of elimination. Previous studies have shown reduced OATP1B1‐mediated uptake of statins into hepatocytes caused by genetic polymorphism or drug interactions 47 . This study shows that HCV infection may also decrease the activity of OATP1B1.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have shown reduced OATP1B1-mediated uptake of statins into hepatocytes caused by genetic polymorphism or drug interactions. 47 This study shows that HCV infection may also decrease the activity of OATP1B1. Although plasma concentrations of proinflammatory cytokines are not available in this study, the lower activity of OATP1B1 observed before the treatment with DAAs (Phase 1) may be related to the intense inflammatory response previously reported in infection by HCV, 3,4,[8][9][10] which could impact the regulation of transporter activity.…”
Section: Articlementioning
confidence: 67%
“…Otherwise, possible associations could be diluted by differences in metabolic and disposition pathways of different statins. For example, common SLCO1B1 and ABCG2 variants differentially affect pharmacokinetics of specific statins [6,[21][22][23][24][25][26][27][28]. Moreover, simvastatin and atorvastatin are metabolized by CYP3A4/5, and fluvastatin is metabolized by the genetically polymorphic CYP2C9 [9,25,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%